Investigating the Efficiency of Government Expenditure on Energy Consumption (Fuel) Subsidy Policy in Indonesia: An Application of Stochastic Frontier Model - Badli, Saiful; Masbar, Raja; Nazamuddin, Nazamuddin; Nasir, Muhammad; Zulham, T.; Saputra, Jumadil; Syahril, Syahril; Noviar, Helmi (International Journal of Energy Economics and Policy, 2020)
The energy consumption is projected to improve living standards and the economy of society. However, for achieving this objective, the government should spend much money in kind of subsidies especially in fuel oil. In several previous studies, they stated that the Indonesia government was experiencing a budget deficit due to their policy about fuel oil subsidy policy. Thus, the purpose of this study is to examine the efficiency of government spending regarding fuel oil subsidy policy in Indonesia. This study designed by using quantitative analysis collected from three data sources, namely Bank Indonesia, Central Bureau of Statistics, and the Ministry of Energy and Mineral Resources. The quarterly data for 21 years which consists of 1996 to 2017 analysed using the stochastic frontier model by assisting statistical software, namely Eviews 10. In this study, we examine the relationship government expenditure via fuel subsidy policy (FUELsubs) on economics growth (GDPpc). Also, the relationship between unemployment (UNEMPLY) and inflation rates (INFL). Besides, for analysing the efficiency of government expenditure on energy consumption (FUEL) subsidy policy in Indonesia, we use the estimation values of the stochastic frontier model through error components, vi and ui. The results of this study found the fuel subsidy policy does not meet the energy subsidy target for the Indonesian economy. Then, there is inefficiency in subsidies that impacts the tradeoff between unemployment and inflation. Keywords: Energy Consumption (Fuel), Fuel Policy, Fuel Subsidy, Government expenditure, Unemployment, Economic Growth. JEL Classifications: Q41, Q43, Q48, E62, E24, O11 DOI: https://doi.org/10.32479/ijeep.9507